EFFECTIVENESS OF DIGITAL POPULATION IDENTITY SERVICES IN BANYUANYAR - Supriyanto, Supriyanto; Rahmadi, Andhi Nur; Wulandari, Dwi Ayu (Jurnal Sosiologi Dialektika Sosial, 2025)
This study analyzes the effectiveness of digital identity issuance services at the Banyuanyar District Office, Probolinggo, based on timeliness, service quality, accessibility, and public satisfaction. by addressing two main research questions: (1) How effective is the implementation of digital identity services? and (2) What are the supporting and inhibiting factors? Using a qualitative approach with data collection through interviews, observations, and document analysis, the findings show improvements in efficiency but also challenges. Time liness has improved compared to conventional services, but technical issues such as network disruptions and limited human resources still cause delays. In terms of service quality, officers follow procedures, but the lack of public socialization makes it difficult for some groups, such as the elderly, to use the system independently. Accessibility is adequate for those with stable internet, but citizens in remote areas still need to visit the district office. Public satisfaction is generally positive, but technical difficulties such as document upload failures and slow system responses remain concerns. To enhance service effectiveness, improvements in digital infrastructure, skilled personnel, and broader public outreach are needed.